Assessment of Prosodic Communicative Efficiency in Parkinson's Disease As Judged by Professional Listeners. (28th July 2011) - Martens, Heidi; Van Nuffelen, Gwen; Cras, Patrick; Pickut, Barbara; De Letter, Miet; De Bodt, Marc
Abstract : This study examines the impact of Parkinson's disease (PD) on communicative efficiency conveyed through prosody. A new assessment method for evaluating productive prosodic skills in Dutch speaking dysarthric patients was devised and tested on 36 individuals (18 controls, 18 PD patients). Three professional listeners judged the intended meanings in four communicative functions of Dutch prosody: Boundary Marking, Focus, Sentence Typing, and Emotional Prosody. Each function was tested through reading and imitation. Interrater agreement was calculated. Results indicated that healthy speakers, compared to PD patients, performed significantly better on imitation of Boundary Marking, Focus, and Sentence Typing. PD patients with a moderate or severe dysarthria performed significantly worse on imitation of Focus than on reading of Focus. No significant differences were found for Emotional Prosody. Judges agreed well on all tasks except Emotional Prosody. Future research will focus on elaborating the assessment and on developing a therapy programme paralleling the assessment.